Efforts to Improve the Quality of Movement Activities of Physical Education, Sports and Health, During the Covid-19 Pandemic - Setyawan, Pradibta Buyung; La Kamadi; Haeruddin, Sofyan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The COVID-19 pandemic has changed our lifestyles. One of them is the world of education. The learning process is hampered, but new innovations emerge in the world of education that indirectly direct education in a more advanced direction by incorporating the world of information and communication technology into education through technological pedagogical content knowledge. Learning currently uses more online learning that utilizes technology, especially internet networks, and reduces the movement activities of students while learning. Physical Education, Sports, and Health are the most challenged by network learning due to the emphasis on movement activities, whereas network learning is more like having students sit in front of the electronic devices used. This also causes a decrease in the value of psychomotor movements. Even if learning is carried out face-to-face, several obstacles are encountered, especially the limited time for face-to-face meetings at school, forcing educators to condense the material to be delivered. In practice, learning with very limited time in the field so as to get students' psychomotor scores for student worksheets requires students to make video recordings in accordance with the material being taught. The main objective of this subject for elementary school age is to increase students' movement activities.